A new species of Bactrocera Macquart reared from Solanum khasianum Clarke in northern India and a new synonym - Singh, Maneesh Pal; Gupta, Divender; Hancock, David Lawrence; Sharma, Isha; Sharma, Prem Lal (Zootaxa, 2023)
A new species of genus Bactrocera Macquart, Bactrocera (Bactrocera) prabhakari Maneesh, Gupta & Hancock, sp. n., is described from Himachal Pradesh, Northern India, reared from Solanum khasianum Clarke commonly known as medicinal solanum or Dutch eggplant. This species resembles Bactrocera latifrons (Hendel) and an updated key to Indian fruit flies of subgenus Bactrocera Macquart is provided. Bactrocera yoshimotoi (Hardy) (= B. luteicinctuta Ito, syn. nov.) in newly recorded from Himachal Pradesh in northern India and variability in B. scutellaris (Bezzi) is discussed together with illustrations.